Community Empowerment in Reducing Used Oil Waste into Environmentally Friendly Soap Products: Pemberdayaan Masyarakat dalam Mengurangi Limbah Minyak Bekas menjadi Produk Sabun Ramah Lingkungan - Puspita, Dian; Sulistiana, Devita (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2025)
The community service program conducted in Sukosewu Hamlet, Sukosewu Village, Gandusari District, Blitar Regency, aims to provide solutions for addressing the issue of used cooking oil waste while simultaneously reducing the environmental pollution caused by its use and promoting product diversification among the local Women’s Empowerment Group (PKK). The training and counseling/socialization methods were carried out for two months to the PKK group. The outreach took place from May to June 2024 in Sukosewu Hamlet, where participants were educated on environmentally friendly methods of processing soap from used cooking oil. Direct mentoring was provided to support the participants, which successfully resulted in the production of eco-friendly soap, contributing to improving the local economy. Additionally, the PKK members gained a deeper understanding of the harmful effects of used cooking oil on health and the environment thanks to this program. Ultimately, participants were also trained in the proper disposal of used cooking oil waste and how to utilize it to prevent environmental pollution. From this mentoring activity, a new product was produced, namely environmentally friendly soap, and public awareness began to grow regarding the importance of protecting the surrounding environment which can increase the economic value (income) of the community, especially mothers in the PKK group.